2018
DOI: 10.1016/j.jacc.2017.10.052
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review for the 2017 AHA/ACC/HRS Guideline for Management of Patients With Ventricular Arrhythmias and the Prevention of Sudden Cardiac Death

Abstract: Evidence from 6 studies of 1138 asymptomatic patients were identified. Brugada syndrome with inducible VA on electrophysiological study was identified in 390 (34.3%) patients. To minimize patient overlap, the primary analysis used 5 of the 6 studies and found an odds ratio of 2.3 (95% CI: 0.63-8.66; p=0.2) for major arrhythmic events (sustained VAs, sudden cardiac death, or appropriate ICD therapy) in asymptomatic patients with Brugada syndrome and inducible VA on electrophysiological study versus those withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Whether EPS inducibility is a predictor of arrhythmic events in BrS patients with previous syncope/sudden death or an independent character remains in dispute (Brugada et al, 2002 , 2004 ; Priori et al, 2002 ; Giustetto et al, 2009 ). In the 2017 AHA/ACC/HRS guideline for ventricular arrhythmias and SCD, an EPS with programmed ventricular stimulation using single or double extrastimuli may be considered for further risk stratification in asymptomatic and spontaneous type 1patients (Kusumoto et al, 2017 ). Newly studies suggested that extent of substrate is the only independent predictor of inducibility of VT or VF and may contribute to a new marker for risk stratification and therapy (Pappone et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether EPS inducibility is a predictor of arrhythmic events in BrS patients with previous syncope/sudden death or an independent character remains in dispute (Brugada et al, 2002 , 2004 ; Priori et al, 2002 ; Giustetto et al, 2009 ). In the 2017 AHA/ACC/HRS guideline for ventricular arrhythmias and SCD, an EPS with programmed ventricular stimulation using single or double extrastimuli may be considered for further risk stratification in asymptomatic and spontaneous type 1patients (Kusumoto et al, 2017 ). Newly studies suggested that extent of substrate is the only independent predictor of inducibility of VT or VF and may contribute to a new marker for risk stratification and therapy (Pappone et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of EPS in the risk stratification of BrS patients has been debated for years, yet it still remains controversial owing to inconsistent results among different studies[29,30,35–29] and meta-analyses. [39,40] The reason for different observations in various studies is likely multifactorial, including patient populations (e.g. the percentage of patients with symptoms at presentation, spontaneous versus drug-induced type 1 ECG pattern), different protocols for programmed stimulations (e.g.…”
Section: Advances In Managementmentioning
confidence: 99%
“…This extended monitoring period is associated with an improved diagnostic yield [ 5 ]. The European Society of Cardiology guidelines suggest that patients who have arrhythmia-related symptoms should receive a 24-h ambulatory ECG, in order to detect potential detrimental ventricular arrhythmia and conduction disorders and preventing SCD [ 6 , 7 ]. The most common finding on AECG are ectopic heart beats: premature atrial complexes (PACs) and premature ventricular complexes (PVCs) originating from the atrial and ventricular myocardium, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%